Indonesian Islamic discourse on happiness : a comparative analysis on the views of Muhammad Quraish Shihab and Komaruddin Hidayat - Maulana, Rizal (International Institute of Islamic Thought and Civilization, International Islamic University Malaysia, 2014)
Happiness is subjective with each individual seeking to determine his personal level of spiritual and material happiness. Given the common association between the pursuit of personal happiness and all human endeavours, this research attempts to ascertain the extent to which Indonesian scholars addressed the Islamic perspective of happiness. For this, the research focuses on the thought of two prominent Indonesian Muslim scholars, Quraish Shihab and Komaruddin Hidayat. Both the scholars have thoroughly discussed the issues of psyche and happiness. Their thoughts are generally welcomed by all strata of Indonesian society. Through his deep reflections of the Qur'ān, Quraish Shihab provides an insightful understanding of the meaning of human happiness, while Komaruddin Hidayat explores Islamic philosophy as the basis of defining human happiness and the meaning of life. This study aims to highlight “Indonesian happiness” by referring to both scholars who share similarities as well as differences in their study of Islam. The study adopts the qualitative method for collecting and analysing the data. The study is based primarily on library research, analysis of data and textual analysis of Quraish Shihab's and Komaruddin Hidayat's works, coupled with an examination of their life. The research concludes that Quraish Shihab and Komaruddin Hidayat are concerned with the scientific accuracy and the objective study of the human purpose in life. They offer definitions on happiness that comply with some systematic and empirical studies. They advocate that happiness is a choice that can be emulated, and that to receive happiness is a blessing and to give happiness is a gift.